Impact of Power Ultrasound on Antihypertensive Activity, Functional Properties, and Thermal Stability of Rapeseed Protein Hydrolysates - Asif Wali; Haile Ma; Muhammad Shahnawaz; Khizar Hayat; Jian Xiaong; Li Jing (Journal of Chemistry)
The effects of power ultrasound pretreatments on the degree of hydrolysis (DH), angiotensin-I-converting enzyme (ACE) inhibitory activity, amino acid composition, surface hydrophobicity, protein solubility, and thermal stability of ACE inhibition of rapeseed protein hydrolysates were evaluated. Ultrasonic pretreatments before enzymolysis in terms of power and exposure time increased the DH and ACE inhibitory activities over the control (without sonication). In this study, maximum DH 22.07% and ACE inhibitory activity 72.13% were achieved at 600 W and 12 min pretreatment. Compared to the hydrolysates obtained without sonication, the amino acid profile of ultrasound pretreated hydrolysates showed significant changes particularly in the proline content and hydrophobic amino acids with an increased rate of 2.47% and 6.31%, respectively. Ultrasound pretreatment (600 watts, 12 min) improved functional properties of protein hydrolysates over control by enhancing surface hydrophobicity and solubility index with an increased rate of 130.76% and 34.22%. Moreover, the stability test showed that the ACE inhibitory activity remains stable against heat treatments. However, extensive heat, prolonged heating time, and alkaline conditions were not in the favor of stability test, while under mild heat and acidic conditions their ACE inhibitory activities were not significantly different from unheated samples.